Mass transport in PEM water electrolysers: A review. (1st January 2022) - Maier, M.; Smith, K.; Dodwell, J.; Hinds, G.; Shearing, P.R.; Brett, D.J.L.
Abstract: While hydrogen generation by alkaline water electrolysis is a well-established, mature technology and currently the lowest capital cost electrolyser option; polymer electrolyte membrane water electrolysers (PEMWEs) have made major advances in terms of cost, efficiency, and durability, and the installed capacity is growing rapidly. This makes the technology a promising candidate for large-scale hydrogen production, and especially for energy storage in conjunction with renewable energy sources – an application for which PEMWEs offer inherent advantages over alkaline electrolysis. Improvements in PEMWE technology have led to increasingly high operational current densities, which requires adequate mass transport strategies to ensure sufficient supply of reactant and removal of products. This review discusses the current knowledge related to mass transport and its characterisation/diagnosis for PEMWEs, considering the flow channels, liquid-gas diffusion layer, and polymer electrolyte membrane in particular. Highlights: Discussion of mass transport aspects in PEM water electrolysers. Review of flow-field geometries, mass flux, and flow regimes. The most common liquid-gas diffusion layer materials are introduced and relevant scientific literature is discussed. Proton and water transport in the Nafion membrane is reviewed.